Drosophila SMN complex proteins Gemin2, Gemin3, and Gemin5 are components of U bodies. - Cauchi, R; Sanchez-Pulido, L; Liu, J (2010)
Uridine-rich small nuclear ribonucleoproteins (U snRNPs) play key roles in pre-mRNA processing in the nucleus. The assembly of most U snRNPs takes place in the cytoplasm and is facilitated by the survival motor neuron (SMN) complex. Discrete cytoplasmic RNA granules called U bodies have been proposed to be specific sites for snRNP assembly because they contain U snRNPs and SMN. U bodies invariably associate with P bodies, which are involved in mRNA decay and translational control. However, it remains unknown whether other SMN complex proteins also localise to U bodies. In Drosophila there are four SMN complex proteins, namely SMN, Gemin2/CG10419, Gemin3 and Gemin5/Rigor mortis. Drosophila Gemin3 was originally identified as the Drosophila orthologue of human and yeast Dhh1, a component of P bodies. Through an in silico analysis of the DEAD-box RNA helicases we confirmed that Gemin3 is the bona fide Drosophila orthologue of vertebrate Gemin3 whereas the Drosophila orthologue of Dhh1 is Me31B. We then made use of the Drosophila egg chamber as a model system to study the subcellular distribution of the Gemin proteins as well as Me31B. Our cytological investigations show that Gemin2, Gemin3 and Gemin5 colocalise with SMN in U bodies. Although they are excluded from P bodies, as components of U bodies, Gemin2, Gemin3 and Gemin5 are consistently found associated with P bodies, wherein Me31B resides. In addition to a role in snRNP biogenesis, SMN complexes residing in U bodies may also be involved in mRNP assembly and/or transport.